Characterization of lesions of nutritional congenital goitre in cattle - Colque Caro, Luis Adrián; Acuña, Francisco; Aguirre Castro, Laura Sabrina; Avellaneda Cáceres, Agustín; Barbeito, Claudio Gustavo; Signorini Porchiett, Marcelo Lisandro; Moore, Prando Dadin; Micheloud, Juan Francisco (Elsevier, 2023)
There are few studies that classify and characterize the morphometric and immunohistochemical features of goitre in bovine thyroid glands (TGs). We investigated 39 bovine TGs (fetuses [9], stillbirths [18], neonates [12]) born to dams with low T4 hormone levels and no iodine supplementation and 10 (fetuses [3], stillbirths [3], neonates [4]) born to dams with normal T4 levels and supplemented with iodine. Body weight (BW), TG weight (TGW), TGW:BW ratio and histological lesions were determined. The TGs were classified histopathologically as normal gland (G0), mild goitre (G1), moderate goitre (G2) or severe goitre (G3). Various morphological and morphometric parameters were calculated from microscopic images using image analysis software. Immunohistochemistry was performed to detect proliferating cell nuclear antigen (PCNA). There were significant differences in the TGW:BW ratio among groups (P <0.05): 0.3 ± 0.1 in G0, 0.5 ± 0.3 in G1, 0.8 ± 0.3 in G2 and 1.3 ± 0.7 in G3. In G0, large homogeneous follicles with eosinophilic colloid were seen. In the groups with lesions (G1, G2 and G3), heterogeneity in follicle shape and size, height and area of thyroid follicular cells, height of thyroid follicular epithelium and PCNA immunolabelling were directly related to histopathological grade, with significant differences among groups (P <0.001), gradually increasing from G1 to G3 compared with G0. The TGW:BW ratio and histological grade were positively correlated (P = 0.008).